Clinical Application and Nursing Management of Suction Drains in Postoperative Patient Care - Alherz, Sughra Salman; Diena Mahboob Alsamti,; Majed Ibrahim Mobarki,; Rehab Hassan Ahmed Ismail,; Ali Ismail Gaisi,; Hind Saad Altamimi,; Nada Hussein Taher Qaisi,; Latifa Mohsen Al-Harbi,; Edrees Mohammed Mohammed Awaji,; Reem Omar Mohammed Al-Anzi, (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Suction drains are a fundamental component of postoperative care across surgical specialties, designed to evacuate fluid collections (e.g., blood, serous fluid, pus) and reduce complications like seroma, hematoma, and infection. They also serve a diagnostic role, providing early warning of hemorrhage or anastomotic leak. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to detail the clinical applications, technical considerations, and comprehensive nursing management of suction drains in postoperative patients, emphasizing an evidence-based and interprofessional approach. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A synthesis of current literature and clinical guidelines is presented, covering the indications, contraindications, and equipment (closed vs. open systems). The technique for drain placement, maintenance (including stripping, emptying, and site care), and monitoring protocols are described. Complications and strategies to enhance team-based outcomes are discussed. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Suction drains are indicated for managing dead space, monitoring anastomoses, and controlling output after extensive dissections or in septic cavities. Closed systems (e.g., Jackson-Pratt) are preferred for sterility and output measurement. Effective management requires meticulous technique for placement, regular monitoring of output character/volume, and diligent site care to prevent infection. Complications include occlusion, infection, displacement, and tissue erosion. Evidence suggests prophylactic drain use is not universally beneficial and should be selective. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> While suction drains are valuable surgical adjuncts, their use must be judicious. Optimal outcomes depend on proper selection, correct technique, vigilant interprofessional monitoring, and timely removal to maximize benefits and minimize risks.